Intra- and Interobserver Variability in Ultrasound Measurement of Testicular Volumes in Pubertal Boys - Frank-Mattias Schäfer; Daniel Bürgener; Maximilian Stehr; Oliver Rompel (MDPI AG, 2024)
Accurate measurement of testicular volume (TV) in boys is an important tool in clinical practice, e.g., in varicocele treatment. This study aims to assess the degree of intra- and interobserver variability of testicular volume measurements. In a prospective study, boys between 11 and 17 years of age without testicular pathology were enrolled. Testicular ultrasound was performed by three investigators (A: pediatric radiologist; B: pediatric surgery/urology resident; C: pediatric urologist). Intraobserver variability was calculated in investigators B and C and interobserver variability between all three investigators. A total of 30 boys were enrolled. Mean intraobserver variability in both observers was +0.3% with a range of −39.6 to 51.5%. The proportion of measurements with a difference >20% was 18.6%. The mean interobserver variability was −1.0% (range: −74.1% to 62.8%). The overall proportion of measurements with a difference >20% was 35%. A lower testicular size of < 4 mL showed a significantly higher rate of >20% difference in both the intraobserver group (31.1% vs. 14.4%; p = 0.035) and the interobserver group (63.2% vs. 26.2%; p = 0.000031). Furthermore, the rate of >20% difference was significantly lower in obese compared to non-obese patients in both the intraobserver (2.8% vs. 22.4%; p = 0.0084) and the interobserver group (24% vs. 40.8%, p = 0.0427). Both intraobserver and interobserver variability in ultrasound-based TV measurements in pubertal boys contain a relevant degree of uncertainty that renders them unsuitable for individualized follow-up care. At the cohort level, however, mean differences in ultrasound-based TV measurements are low enough to make ultrasound comparisons reasonable.